2005
DOI: 10.1111/j.1523-1755.2005.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate is toxic to renal tubular cells only at supraphysiologic concentrations

Abstract: This study shows that oxalate is toxic to renal tubular cells, but only at supraphysiologic concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
4
44
0
3
Order By: Relevance
“…It is well known that the high rate of oxalate excretion among patients with PH results in supersaturation of CaOx in the urine, favoring CaOx crystal formation (16). CaOx crystals not only aggregate in the urinary space, producing stones (urolithiasis), but they also interact with the renal tubule epithelium and deposit in the renal interstitium (nephrocalcinosis), where they can induce an inflammatory response and progressive interstitial fibrosis that can compromise kidney function (17)(18)(19)(20). In this cohort, higher urinary oxalate excretion at both diagnosis and follow-up were associated with poorer renal outcome.…”
Section: Discussionmentioning
confidence: 90%
“…It is well known that the high rate of oxalate excretion among patients with PH results in supersaturation of CaOx in the urine, favoring CaOx crystal formation (16). CaOx crystals not only aggregate in the urinary space, producing stones (urolithiasis), but they also interact with the renal tubule epithelium and deposit in the renal interstitium (nephrocalcinosis), where they can induce an inflammatory response and progressive interstitial fibrosis that can compromise kidney function (17)(18)(19)(20). In this cohort, higher urinary oxalate excretion at both diagnosis and follow-up were associated with poorer renal outcome.…”
Section: Discussionmentioning
confidence: 90%
“…8 COM crystals could modify the membrane structure and function, activate ROS, cause oxidant/antioxidant imbalance, lead to mitochondrial dysfunction, and increase lipid peroxidation, 19 which induces apoptotic or necrotic cell death in renal epithelial cells. 9,[47][48][49] COD is the second most common component of CaOx renal stones, although existing studies on the toxic effect of COD crystals on renal epithelial cells are inadequate. Our previous study reported that nano-COD induced higher toxicity on Vero cells compared with the micro-sized crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid crystal binding did not depend on anionic cell surface binding molecules (79). CaOx dihydrate (COD) nucleated directly on the cell surface via their [101] face (80), to become associated with the membrane through their [100] face (81,82). Crystal binding stimulated additional crystal attachment and was inhibited by arachidonic acid or other compounds that raise intracellular cAMP (83).…”
Section: Crystal-cell Interactionsmentioning
confidence: 93%
“…A recent animal study demonstrated that the production of free radicals probably is the consequence of oxalate-mediated renal tubular injury rather than the initiating cause (99). In cell culture studies, it was found that oxalate cannot become very high in the presence of physiologic amounts of calcium (100,101) and that oxalate seemed to be relatively harmless in the absence of calcium (101). Accumulating evidence suggests that the assumed oxalate-induced cell injury in fact often is caused by crystals (75,102,103).…”
Section: Crystal-cell Interactionsmentioning
confidence: 99%